A Tale of Two Systems: Cardiac Cephalalgia vs Migrainous Thoracalgia. Issue 2 (6th May 2014) - Mathew, Paul G.; Boes, Christopher J.; Garza, Ivan
<x xml:space="preserve">Abstract</x> The practice of headache medicine is challenging, and excluding secondary causes of headaches is essential for proper diagnosis and treatment. The evaluation of secondary headaches often leads to investigations involving organ systems other than the nervous system. As such, headache, which is typically thought to be neurologic in origin, can be a manifestation of cardiac pathology in the form of cardiac cephalalgia. Conversely, chest pain, which is typically thought to be cardiac in origin, could be a manifestation of a neurologic disease process in the form of atypical migraine aura. In the presented cases, we demonstrate headaches that involve cardiac and neurologic pathology with atypical presentations.